Ogłoszenie upadłości oskarżonego a orzeczenie obowiązku naprawienia szkody w procesie karnym - Waga, Joanna (PRAWO i WIĘŹ, 2026)
This paper concerns the impact of declaring bankruptcy by an accused person on the possibility of including in a conviction an order to compensate for damage caused by crime. Despite a considerable amount of criminal proceeding concernig such a configuration this topic was not the subject of any analysis of judicature or doctrine by far. The purpose of the study is to answer the question if – and if so, in which cases – criminal judge should refrain from ruling an order to compensate for damages. The analysis is focused on an influence of prohibition on pursuing a claim after declaring bankruptcy (art. 263 of Insolvency Law) on examination of the application for repair based on art. 46 of Criminal Code. Then it is completed by reference to comments regarding application of art. 415 of Code of Criminal Proceedure in case of notification, inclusion and rejection of inclusion claim of compensation damage caused by crime on a list of claims. The effect of the study is specification of cases, when including an order to compensate for damages in conviction occurs as an unacceptable.